The tumor necrosis factor-α inhibitor golimumab in the treatment of rheumatoid arthritis - Natalia Vladimirovna Chichasova (Современная ревматология, 2014)
The tumor necrosis factor-α (TNF-α) golimumab (GLM), that is a fully human monoclonal anti-body, was registered in Russia in 2012 to treat rheumatic diseases, such as rheumatoid arthritis (RA), ankylosing spondylitis, and psoriatic arthritis. Its distinguishing characteristics are a high affinity for TNF-α and easiness-to-use: the drug as a 0.5-ml solution is injected subcutaneously once monthly. The registration of the medication was followed by the implementation of a massive program of clinical trials. The randomized placebo-controlled GO-FORWARD, GO-BEFORE, and GO-AFTER studies have indicated that GLM is effective in patients with RA from different subgroups and has a favorable safety profile as compared to that of the entire class of biological agents. According to the data of these studies, GLM had a positive effect on the functional status and quality of life in patients with RA: there was a significantly greater decrease in HAQ scores in both the early and long open treatment phases (to 5 years) and in fatigability than in the control group (p=0.032), physical and mental health improvements, as shown by the SF-36 questionnaire, and a significant reduction in disability.